Upaya Guru Pendidikan Agama Islam Dalam Meningkatkan Kualitas Membaca Al Qur’an Siswa Madrasah Ibtidaiyah Al Imron Pakamban Laok Pragaan Sumenep - Firdauzi, Hikmatul; El-Faradis, Fayruzah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
This research aims to describe the efforts of Islamic Religious Education (PAI) teachers in improving the quality of Al-Qur'an reading for Madrasah Ibtidaiyah (MI) Al-Imron Pakamban Laok Pragaan Sumenep students, as well as to identify the obstacles faced by PAI teachers in this process. The Koran, as a source of Divine revelation, plays a central role in a Muslim's life, which requires the ability to read its verses well and correctly. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions using source triangulation and technical triangulation to ensure the validity of the data. The research results show that PAI teachers' efforts to improve the quality of students' reading of the Al-Qur'an involve various methods, such as lectures, exercises, questions and answers, as well as practice reading the Al-Qur'an before lessons begin. However, several barriers were also identified, including lack of student interest, lack of encouragement from families, and limited time in class. In conclusion, this research provides a comprehensive picture of efforts and obstacles in improving the quality of Al-Qur'an reading for MI Al-Imron Pakamban Laok Pragaan Sumenep students, as well as providing valuable insights for the development of Islamic religious education in the school environment.